ANALYSIS OF CONSENSUAL HALLUCINATION PHENOMENA IN NETSPEAK, NETLINGO PRACTICE, AND MILLENNIAL GENERATION NETIQUETTE - Wahyuni Choiriyati; Dinda Rakhma Fitriani; Leo Susanto (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
This phenomenological research aims to uncover textual digital communication practices involving netspeak and netlingo also forms of millennial consensual hallucinations on social media. The novelty of this research is the millennial generation category, which has new netiquette as a consensus. Research obtained through interviews with informants concluded the practice of textual communication. The first practice is netlingo, which produces a speech-language which is then turned into text, such as expressions of surprise that are modified in written form. The form of netspeak concluded from this research is capital letters to express communication emotions. Textual communication used on social media such as Instagram and Whatsapp cannot make a sound but has become a mass convention for social media users. This research puts the concept of netspeak and netlingo that can encourage consensual hallucinations. These hallucinations are in the form of the assumption that social media is a free and equal place, so there are no restrictions like the real world. Hallucinations for millennials are assumed to be equality in communication